Integrated sand management for effective hydrocarbon flow assurance - Oyeneyin, Babs (Amsterdam : Elsevier, 2014)
This Handbook provides solutions to the fundamental issues associated with wells and reservoirs experiencing sanding problems, especially in deepwater environments. Sand Management is a massive challenge for the petroleum industry as it extends its exploration activities to new frontiers. Challenging ultra deepwater, High Pressure-High Temperature (HP-HT) and Arctic environments require engineers to drill more complex wells and manage more complex reservoirs, the majority of which are prone to massive sand production. Covering such fundamentals as how to maximize individual wells and field development performance, as well as how to minimize operational cost, non-productive time and guarantee flow assurance across the entire composite production system from reservoirs through the wellbore to the topside and flow lines, this handbook explains that the biggest challenge facing operators is the shortage of sand management personnel and helps companies realize the value of their assets.
1. Unsteady-state Flow2. Steady-state Flow; 3. Semi-Steady State Flow; Application Option; 'Steady' Flow Region; 2.7.4. Volume-Averaged Pressure; 2.7.5. Evaluation of Well Performance; 2.7.5.1. Well Inflow Performance; 2.7.5.2. Productivity Index; 2.8. Productivity in Horizontal Wells; 2.9. Nodal Analysis; 2.9.1. Establishment of IPR Curve (Figure 2.21); 2.9.2. Tubing Performance Correlation; 2.9.3. Frictional Pressure Drop; 2.10. Flow Assurance Management; 2.10.1. Scale Management; 2.10.1.1. Formation and Prediction of Mineral Scales; 1. Calcium Carbonate: Formation and Prediction.
CIP data; resource not viewed.
Includes bibliographical references and index.
Keywords: Oil wells -- Sand control; TECHNOLOGY & ENGINEERING -- Mining; Oil wells -- Sand control; Electronic books